Perancangan Jaringan Konfigurasi Wireless Access Point Menggunakan Packet Tracer 6.2 Pada SMKN 1 Semende Darat Laut - Saputra, Agung; Hidayat, Kemas Muhammad Wahyu (Jurnal Nasional Ilmu Komputer, 2024)
The use of computer networks for decades has been used to connect business processes in companies, universities, between cities, or between regions. Initially, computer networks used cables to connect, but slowly this changed towards the use of wireless networks. The application of wireless networks can have a significant impact in the process of change that can allow people to expand their work scope because it is not related to cables. M. Setiawan Hidayat (2009) explains that there are many real benefits from the use of wireless networks, especially those related to problems found in wired networks. One of the benefits of using wireless networks is the relative absence of distance limitations. Usually, cables must be installed following the shape of walls, crossing floors, and so on. This research method uses the Network Development Life Cycle (NDCL) method to design a network using an access point configuration that can facilitate data transmission and speed up a connection, and the access point can connect a local network with a wireless network. Wireless networks eliminate this problem because they are line-of-sight. Wireless Local Area Networks (WLANs) are used to reach LAN areas that are difficult to reach with cables and also to reach mobile users. They can eliminate or even eliminate the use of cables, which can be quite disruptive in the complex installation of connecting more than one computer or mobile user.